Tram track maintenance-planning by gauge degradation modelling - Ahac, Maja; Lakušić, Stjepan (Transport, 2015)
Tram track system management is a complex, costly and interdisciplinary process. It involves construction, monitoring and maintenance of track infrastructure and rolling stock, and public transport organization. Track management cost reduction requires development of a modern management system that is based on integration and mutual complementarity of engineering and maintenance activities. The first step of its establishment is increasing the proportion of planned predictive-preventive track maintenance at the expense of corrective maintenance. This requires creation of a maintenance-planning model. Its basic prerequisite is the development of a mathematical model of tram track degradation during exploitation. The research presented in this paper describes the creation of mechanisticempirical models for tram tracks (narrow) gauge degradation by adopting the modelling methodology used on the classic railway constructions. Two types of tram tracks are observed: tracks with indirect elastic rail fastening system and stiffer direct elastic rail fastening system. These models represent the first step towards establishing a predictive maintenance system on Zagreb tram tracks.